Circulating tumor cell characterization of lung cancer brain metastases in the cerebrospinal fluid through single‐cell transcriptome analysis. Issue 8 (15th December 2020) - Ruan, Haoyu; Zhou, Yihang; Shen, Jie; Zhai, Yue; Xu, Ying; Pi, Linyu; Huang, Ruofan; Chen, Kun; Li, Xiangyu; Ma, Weizhe; Wu, Zhiyuan; Deng, Xuan; et al.
Abstract: Background: Brain metastases explain the majority of mortality associated with lung cancer, which is the leading cause of cancer death. Cytology analysis of the cerebrospinal fluid (CSF) remains the diagnostic gold standard, however, the circulating tumor cells (CTCs) in CSF (CSF‐CTCs) are not well defined at the molecular and transcriptome levels. Methods: We established an effective CSF‐CTCs collection procedure and isolated individual CSF cells from five lung adenocarcinoma leptomeningeal metastases (LUAD‐LM) patients and three controls. Three thousand seven hundred ninety‐two single‐cell transcriptomes were sequenced, and single‐cell RNA sequencing (scRNA‐seq) gene expression analysis was used to perform a comprehensive characterization of CSF cells. Results: Through clustering and expression analysis, we defined CSF‐CTCs at the transcriptome level based on epithelial markers, proliferation markers, and genes with lung origin. The metastatic‐CTC signature genes are enriched for metabolic pathway and cell adhesion molecule categories, which are crucial for the survival and metastases of tumor cells. We discovered substantial heterogeneity in patient CSF‐CTCs. We quantified the degree of heterogeneity and found significantly greater among‐patient heterogeneity compared to among‐cell heterogeneity within a patient. This observation could be explained by spatial heterogeneity of metastatic sites, cell‐cycle gene, and cancer‐testis antigen (CTA) expression profiles as well as the proportion of CTCs displaying mesenchymal and cancer stem cell properties. In addition, our CSF‐CTCs transcriptome profiling allowed us to determine the biomarkers during the progression of an LM patient with cancer of unknown primary site (CUP). Conclusions: Our results will provide candidate genes for an RNA‐based digital detection of CSF‐CTCs from LUAD‐LM and CUP‐LM cases, and shed light on the therapy and mechanism of LUAD‐LM. Abstract : Our study firstly investigated CSF‐CTCs characteristics of five LUAD‐LM patients and one CUP‐LM patient. CSF‐CTCs enriched metabolism and cell‐adhesion pathways. CSF‐CTCs exhibited heterogeneity manifested by cell cycle, mesenchymal and cancer stem cell, and cancer‐testis antigen properties